1999
DOI: 10.1063/1.371786
|View full text |Cite
|
Sign up to set email alerts
|

Sputtered Sm–Co films: Microstructure and magnetic properties

Abstract: Films of Sm–Co have been sputtered on heated polycrystalline Al2O3 substrates. The effect of variations of the Sm content on microstructure and hard magnetic properties was studied for otherwise constant process parameters. As generally observed, the samples possess a magnetic texture where the easy magnetization directions of the grains lay preferably in the film plane. For a lower Sm content the TbCu7-type structure is stabilized and for a higher Sm content the CaCu5-type structure is stabilized. The crossov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 10 publications
1
23
1
Order By: Relevance
“…Due to the thickness and high crystallinity, also the K b peak of the MgO substrate is visible. In Figure 1(b), the region around the SmCo (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) peak is shown, for films grown with a sputter pressure of 1.5, 3.0, 7.5, and 10.5 Â 10 À3 mbar. Clearly visible is that, with decreasing pressure, the peaks shift to a higher angle.…”
Section: A Composition and Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the thickness and high crystallinity, also the K b peak of the MgO substrate is visible. In Figure 1(b), the region around the SmCo (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) peak is shown, for films grown with a sputter pressure of 1.5, 3.0, 7.5, and 10.5 Â 10 À3 mbar. Clearly visible is that, with decreasing pressure, the peaks shift to a higher angle.…”
Section: A Composition and Morphologymentioning
confidence: 99%
“…However, for various applications, growing Sm-Co thin films from alloy targets is a desirable option since only one deposition source is needed. Still, as far as we know, relatively few groups [12][13][14][15][16][17][18][19][20] have reported on the growth of Sm-Co thin films from single alloy targets. The purpose of this work is to show what the properties are of such films, grown on MgO(100), and in a range of pressures.…”
Section: Introductionmentioning
confidence: 99%
“…Though extensive research has been done on the films of Sm-Co binary and ternary alloys, very few results are reported on sputtered thin film of Sm 2 (CoCuFeZr) 17 composition. [17][18][19][20] The studies performed on thin films of this composition are mainly focused on the effect of sputtering parameters such as gas pressure, substrate temperature, sputtering gas, etc., on the magnetic properties. 17,19 The maximum coercivity of $0.4 to 1 T has been reported up to now by Hedge et al for Sm(CoCuFeZr) z thin film sputtered at 350 C. 20 The coercivity is attributed to the texture growth of the film with the crystallite c-axis lying in the film plane.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20] The studies performed on thin films of this composition are mainly focused on the effect of sputtering parameters such as gas pressure, substrate temperature, sputtering gas, etc., on the magnetic properties. 17,19 The maximum coercivity of $0.4 to 1 T has been reported up to now by Hedge et al for Sm(CoCuFeZr) z thin film sputtered at 350 C. 20 The coercivity is attributed to the texture growth of the film with the crystallite c-axis lying in the film plane. However, to the best of our knowledge, no single study has been reported so far on the development of cellular microstructure growth in Sm(CoCuFeZr) z films.…”
Section: Introductionmentioning
confidence: 99%
“…One of the major requirements of such applications is the need to deposit permanent magnetic films with high coercivity and large energy products on silicon substrates. Among the rare earth group of permanent magnetic films SmCo films offer excellent intrinsic and extrinsic magnetic properties [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%